Evaluation and Influence of Recycled Concrete Aggregate Base Layers on Hma Pavement Performance - (:unkn) unknown (My University, 2018)
This research investigated the influence of the RCA base layers on the HMA pavement performance as compared with CA base layers using laboratory tests on collected base layer materials and field tests on corresponding pavement sections. Field and laboratory testing programs were conducted to investigate RCA and CA base layer materials in which identified test sections at the selected pavement sites were subjected to testing using FWD, walking profiler, and DCP. Visual distress surveys were also conducted at the selected pavement sections. RCA and CA base layer samples were collected from these pavement sites and were subjected to a laboratory testing program including: particle size analysis, Micro-Deval abrasion test, absorption, and specific gravity. Laboratory tests indicated that the investigated RCA base layer materials are in general “finer” than the CA base materials based on the FM and GN values. The RCA base layer materials also possessed higher absorption values compared with CA base materials. In terms of resistance to abrasion, Micro-Deval abrasion test results showed that RCA and CA base layer materials exhibited high mass loss, in general, compared with a mean mass loss of 15.05% for Wisconsin virgin coarse aggregates. Field tests evaluated the strength and modulus of the investigated RCA and CA base materials and pavement test sections based on DCP and FWD tests. The DCP test results indicated that the CBR and layer moduli values of both RCA and CA base layer types are comparable. The CBR and base layer modulus values obtained from the results of the DCP tests indicated in general good strength and modulus properties of the investigated RCA and CA bases. The FWD test results showed variability in pavement surface deflections within individual test sections and among the various pavement test sections. In general, less deflection D0 values exhibited by pavement test sections with RCA base layers compared with those with CA base layers. The back-calculated moduli for the RCA and CA base layers (EBase) exhibited significant variability within individual pavement test sections and among pavements. Comparison of the back-calculated layer moduli values Ebase for RCA and CA base layer pavement show that there are very high values exhibited by RCA base layers for example at STH 78, which could be attributed to the tufa formation. The results of the visual distress surveys and pavement profile measurements (in terms of calculated PCI and IRI) for investigated pavement test sections showed variability with classified pavement conditions ranging from poor to good. The HMA pavements with RCA base layers exhibited higher PCI values indicating better pavement quality. The HMA pavements with CA base layers exhibited lower IRI values compared with the HMA pavements with CA base layers indicating a smoother ride quality for HMA pavement with CA base layer.